2022
DOI: 10.1037/pspp0000437
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adult attachment and mental health: A meta-analysis.

Abstract: Attachment theory provides a framework for understanding the correlations among interpersonal relationships, stress, and health. Moreover, adult attachment is an important predictor of mental health. However, there is a lack of systematic reviews that simultaneously examine the associations between adult attachment and both positive and negative indicators of mental health. Consequently, we meta-analyzed 224 studies examining the associations between adult attachment and mental health, using robust variance es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 138 publications
(193 reference statements)
2
19
1
1
Order By: Relevance
“…Concerning the relationship between love addiction and adult attachment, our results showed that only fearful and preoccupied styles showed significant and positive associations with love addiction. This is in line with earlier evidence showing how fearful and preoccupied attachments are associated with different forms of addiction; these two styles of attachment seem to be more frequent in subjects with substance dependence, such as with heroin [ 19 ], alcohol, tobacco, or waterpipes [ 53 ], as well as problematic smartphone use [ 54 ] and social media addiction [ 23 , 55 ], and sexual addiction [ 56 ]. The preoccupied attachment is characterized by fear that others are unavailable in times of need, and involves an anxious search for love and support and dependence on a desire for commitment in relationship, while fearful attachment is characterized by distrust of others’ intentions, compulsive self-reliance, and the low intensitiy of fewer love experiences [ 18 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the relationship between love addiction and adult attachment, our results showed that only fearful and preoccupied styles showed significant and positive associations with love addiction. This is in line with earlier evidence showing how fearful and preoccupied attachments are associated with different forms of addiction; these two styles of attachment seem to be more frequent in subjects with substance dependence, such as with heroin [ 19 ], alcohol, tobacco, or waterpipes [ 53 ], as well as problematic smartphone use [ 54 ] and social media addiction [ 23 , 55 ], and sexual addiction [ 56 ]. The preoccupied attachment is characterized by fear that others are unavailable in times of need, and involves an anxious search for love and support and dependence on a desire for commitment in relationship, while fearful attachment is characterized by distrust of others’ intentions, compulsive self-reliance, and the low intensitiy of fewer love experiences [ 18 , 25 ].…”
Section: Discussionsupporting
confidence: 89%
“…1 ). Attachment anxiety is known to influence general anxiety [ 31 , 32 ] as well as dental-related fear [ 14 ]. While anxiety my not generally be related to non-compliance [ 33 ], an accompanying critical attitude can either be prospectively relevant for discontinuation, or retrospectively used to reduce cognitive dissonance for the decision to terminate SPT.…”
Section: Discussionmentioning
confidence: 99%
“…The attachment styles also predict the quality of mental health. For example, Zhang et al (2022) showed that insecure attachment style highly increased the risk of poor mental health. Therefore, this variable seems likely to be a determinant of well-being in emerging adults.…”
Section: The Emerging Adult's Attachment Stylementioning
confidence: 99%